Boron and salt ion transport in electrically assisted reverse osmosis - Bao, Xian (2022)
Herein, we report a novel electrically assisted reverse osmosis (EARO) process which integrates an electrochemical process with the conventional RO process. We systematically investigated the behaviors of boron and salt ion (i.e., Na+ and Cl−) transporting through a commercial seawater RO (SWRO) membrane in the EARO process under a range of applied voltages by employing an external porous carbon cloth as cathode on the SWRO membrane surface. The SWRO membrane in the EARO process exhibited a significantly enhanced boron rejection of 93.8% under the applied voltage of 4 V compared with the conventional RO process (~75.0%). The enhancement in boron removal efficiency in EARO is mainly attributed to the locally elevated pH near the RO membrane surface caused by water electrolysis. At elevated pH, boron transforms from the uncharged boric acid to negatively charged and sized-increased borate ion and is more favorably rejected by the SWRO membrane. On the other hand, the variation of salt ion rejection was marginal with increasing the applied voltages in EARO. This study demonstrates that the EARO has a great potential to achieve low-chemical and low-cost boron removal in one-pass RO seawater desalination. To make this process more practically feasible, the future efforts need to optimize the development of the electrically conductive feed spacer and the membrane module.